Analysis of the Relationship between Women’s Participation and the Rate of Corruption in the Post-Soviet States - Bektas Baktybayev (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2020)
Corruption remains one of the main problems of Post-Soviet states. Georgia, Belarus, Lithuania, and Latvia are doing relatively well compared to other Post-Soviet states. Popular explanations for high corruption rates are underdevelopment of democratic institutions and the limitation of human rights. However, the lack of women’s participation can be also another factor that could explain the widespread corruption level. According to popular stereotypes, women are considered as more honest and “fairer” gender, which has an impact on the decrease in corruption rate. There is a belief that women have a perception of risk aversion which makes them less likely to engage in corrupt activities. There is no consensus regarding whether women’s participation has an effect on reducing corruption. The purpose of this paper is to test to what extent women’s participation in parliament, school and or with tertiary education, labor force affects corruption rate in Post-Soviet states. The SPSS software was used to assess a relationship between aforementioned variables. According to findings, there is a strong, positive, and statistically significant impact of women enrollment in school and/or with tertiary education on a country’s score in the Corruption Perception Index. I argue that promoting women’s education is the best way to lower corruption in the post-Soviet states.